2015
DOI: 10.4103/1735-9066.164501
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of nursing research utilization in Iran: A systematic review

Abstract: Background:According to professionalization in nursing profession, the nursing researches expanded dramatically and rapidly in a very short period. Research results showed improvement in quality of provided care by using research findings. But there is still a gap between nursing research and practice, which led scientists to explore the barriers and facilitators of research utilization that could affect the application of research results. The aim of this review was to appraise and synthesize evidences of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 34 publications
(50 reference statements)
2
18
0
Order By: Relevance
“…24 It seems that structural defects in support of nurses causes clinical nurses develop a routine work-based approach in practice and refrain from having their own independent intervention. 25 A study by Adib-Hajbaghery et al, in Iran showed that the ethical decisions making by a nurse is also based on routine tasks and physicians' orders. 15 Lack of sufficient self-confidence in decision-making is an important barrier to patient independence which causes patients' dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…24 It seems that structural defects in support of nurses causes clinical nurses develop a routine work-based approach in practice and refrain from having their own independent intervention. 25 A study by Adib-Hajbaghery et al, in Iran showed that the ethical decisions making by a nurse is also based on routine tasks and physicians' orders. 15 Lack of sufficient self-confidence in decision-making is an important barrier to patient independence which causes patients' dissatisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The nursing literature is robust in reporting the challenges for engaging clinical staff in nursing research. Several articles (Chien, Bai, Wong, Wang, & Lu, 2013;Dunning, 2013;Hagan & Walden, 2015;Sanjari, Baradaran, Aalaa, & Mehrdad, 2015;Silka, Stombaugh, Horton, & Daniels, 2012) highlight barriers, which include lack of time, insufficient knowledge or authority, and the perceived absence of organizational leadership support. While time and resources are known to be limited in all levels and roles of nursing, the literature also has shown some differences regarding the facilitators related to nursing research.…”
mentioning
confidence: 99%
“…A survey of 304 nurses working in teaching hospitals in 2003 reported the following: 80.6% had not been involved with the conduct of any research since qualifying as a nurse; 70% of those who had undertaken some research had done it as part of a course; about 30% had never used research in their practice; 44.3% read research once every 2 or 3 months or more frequently; and the main information sources that the majority relied on for practice were nursing textbooks and/or asking the nurse supervisors [ 140 ]. The barriers to research utilization in nursing practice in Iran had been identified as follows: (i) insufficient time to read papers; (ii) inadequate facilities and time to implement research; (iii) limited authority of nurses to change practice and limited cooperation of medical doctors in this regard; (iv) inaccessibility of scientist by whom the nurses could discuss relevant topics; and (v) inadequacy of relevant research [ 140 - 142 ].…”
Section: Resultsmentioning
confidence: 99%